2018
DOI: 10.1002/rcm.8064
|View full text |Cite
|
Sign up to set email alerts
|

Collagen proteins exchange oxygen with demineralisation and gelatinisation reagents and also with atmospheric moisture

Abstract: Studies of δ O values in collagen proteins should avoid extraction methods using acid solutions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 91 publications
(195 reference statements)
0
8
0
Order By: Relevance
“…The investigation of deamidation using mass spectrometry has been wildly applied and reported heavily in the literature; despite this, we are still discovering and learning, not only about the mechanism itself, but also about how the procedures we use during sample preparation and analysis can influence the resulting Q/E measurements, with papers published only recently detailing the effects of well-established extraction procedures. 16,25 When containing glutamic acid were found to have statistically significant differences in ionisation behaviour between ionisation sources and the number of times they were observed, with peptides containing glutamic acid being preferentially ionised by ESI. In addition, it has also been reported that asparagine and aspartic acid containing peptides ionise similarly under ESI conditions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The investigation of deamidation using mass spectrometry has been wildly applied and reported heavily in the literature; despite this, we are still discovering and learning, not only about the mechanism itself, but also about how the procedures we use during sample preparation and analysis can influence the resulting Q/E measurements, with papers published only recently detailing the effects of well-established extraction procedures. 16,25 When containing glutamic acid were found to have statistically significant differences in ionisation behaviour between ionisation sources and the number of times they were observed, with peptides containing glutamic acid being preferentially ionised by ESI. In addition, it has also been reported that asparagine and aspartic acid containing peptides ionise similarly under ESI conditions.…”
Section: Discussionmentioning
confidence: 99%
“…This study highlights the importance of investigating the suitability of analytical methodology to the question being asked: Including the suitability of the proposed mass spectrometric techniques used to answer research questions. The investigation of deamidation using mass spectrometry has been wildly applied and reported heavily in the literature; despite this, we are still discovering and learning, not only about the mechanism itself, but also about how the procedures we use during sample preparation and analysis can influence the resulting Q/E measurements, with papers published only recently detailing the effects of well‐established extraction procedures . When deciding which ionisation source is most suitable for the samples in question, it is important to investigate relative mass spectrometric responses.…”
Section: Discussionmentioning
confidence: 99%
“…Some variability is also introduced by our collagen sampling method, whereby we demineralize the bone but do not gelatinize the collagen, due to potential partial hydrolysis by hot water gelatinization. In addition, halide acid demineralization produces inconsistent results for oxygen isotopic analysis, and further experimentation is needed to delineate the effects of gelatinization and halide acid demineralization on δ 2 H values . The collagen pseudomorph resulting from EDTA decalcification may have some fine‐scale spatial isotopic variability which then becomes incorporated into the different sample aliquots prepared for mass spectrometry (see Reynard and Tuross for further discussion of pretreatments).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, halide acid demineralization produces inconsistent results for oxygen isotopic analysis, and further experimentation is needed to delineate the effects of gelatinization and halide acid demineralization on δ 2 H values. 20 The collagen pseudomorph resulting from EDTA decalcification may have some fine-scale spatial isotopic variability which then becomes incorporated into the different sample aliquots prepared for mass spectrometry (see Reynard and Tuross 9 for further discussion of pretreatments). The average offset uncertainty is ±5.2‰ (1 sd), and the half-width of the prediction interval at 68% confidence is 5.0-5.2‰, which are in excellent agreement and slightly larger than our estimate of the usual error of a δ 2 H measurement, as predicted.…”
Section: Discussionmentioning
confidence: 99%
“…although collagen may offer a more diagenetically robust substrate for δ 18 O measurements of bone tissue compared to bioapatite carbonate, to date there is no consensus quality controls to assess diagenetic alteration in δ 18 Ocoll data (Crowley, 2015(Crowley, , 2014Kirsanow et al, 2008;Tuross et al, 2008;von Holstein et al, 2013). Furthermore, concerns have been raised about isotopic alteration of collagen during collagen extraction and burial (von Holstein et al, 2018).…”
Section: Isotopic Composition Of Bones and Dental Tissuesmentioning
confidence: 99%